Thermal and magnetic evolution of Mercury with a layered Fe-Si(-S) core - Christopher J. Davies; Anne Pommier; Sam Greenwood; Alfred Wilson (Earth and Planetary Science Letters, 2024)

Collapse of Calcareous Silty Clay: Implication of Calcite Content and Wetting Fluid Type - Alfred Wilson Opukumo; Stephanie Glendinning; Collin T. Davie (Geotechnical and Geological Engineering, 2024)

Examining the power supplied to Earth's dynamo by magnesium precipitation and radiogenic heat production - Alfred J. Wilson; Monica Pozzo; Christopher J. Davies; Andrew M. Walker; Dario Alfè (Physics of the Earth and Planetary Interiors, 2023)

Can homogeneous nucleation resolve the inner core nucleation paradox? - Alfred J. Wilson; Dario Alfè; Andrew M. Walker; Christopher J. Davies (Earth and Planetary Science Letters, 2023)

Storm impacts on phytoplankton community dynamics in lakes - Jason D. Stockwell; Jonathan P. Doubek; Rita Adrian; Orlane Anneville; Cayelan C. Carey; Laurence Carvalho; Lisette N. De Senerpont Domis; Gaël Dur; Marieke A. Frassl; Hans‐Peter Grossart; Bas W. Ibelings; Marc J. Lajeunesse; et al. (Global Change Biology, 2020)
In many regions across the globe, extreme weather events such as storms have increased in frequency, intensity, and duration due to climate change. Ecological theory predicts that such extreme events should have large impacts on ecosystem structure and function. High winds and precipitation associated with storms can affect lakes via short‐term runoff events from watersheds and physical mixing of the water column. In addition, lakes connected to rivers and streams will also experience flushing due to high flow rates. Although we have a well‐developed understanding of how wind and precipitation events can alter lake physical processes and some aspects of biogeochemical cycling, our mechanistic understanding of the emergent responses of phytoplankton communities is poor. Here we provide a comprehensive synthesis that identifies how storms interact with lake and watershed attributes and their antecedent conditions to generate changes in lake physical and chemical environments. Such changes can restructure phytoplankton communities and their dynamics, as well as result in altered ecological function (e.g., carbon, nutrient and energy cycling) in the short‐ and long‐term. We summarize the current understanding of storm‐induced phytoplankton dynamics, identify knowledge gaps with a systematic review of the literature, and suggest future research directions across a gradient of lake types and environmental conditions.

In situ impacts of a flooding event on contaminant deposition and fate in a riparian ecosystem - Brittan A. Wilson; Alfred K. Addo-Mensah; Monica O. Mendez (Journal of Soils and Sediments, 2015)

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

Lifetime exposure to arsenic in drinking water and bladder cancer: a population-based case–control study in Michigan, USA - Jaymie R. Meliker; Melissa J. Slotnick; Gillian A. AvRuskin; David Schottenfeld; Geoffrey M. Jacquez; Mark L. Wilson; Pierre Goovaerts; Alfred Franzblau; Jerome O. Nriagu (Cancer Causes & Control, 2010)

Mixing and differentiation in the Oruanui rhyolitic magma, Taupo, New Zealand: evidence from volatiles and trace elements in melt inclusions - Yang Liu; Alfred T. Anderson; Colin J. N. Wilson; Andrew M. Davis; Ian M. Steele (Contributions to Mineralogy and Petrology, 2006)

Spatial statistics for modeling of abundance and distribution of wildlife species in the Masai Mara ecosystem, Kenya - Wilson M. Khaemba; Alfred Stein (Environmental and Ecological Statistics, 2001)